ELECTION OF CONSTITUTIONAL COURT JUDGES AS A GUARANTEE OF CONSTITUTIONAL COURT INDEPEDENCE - Nićiforović, Andjela (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2025)
In a system of government based on the principle of separation and balance of power, the constitutional court is considered to be an autonomous and independent constitutional authority. The independence of the constitutional court also implies the independence of its members from all other power holders and from the state bodies that participated in their election. The election of judges of the Constitutional Court is one of the most important guarantees of its independence. In addition, the selection of the Constitutional Court judges is a guarantee securing its legitimacy, preservation of its function as a politically neutral government, as well as the selection of persons with appropriate professional and personal qualities. The paper analyzes the legal requirements that judges must meet in order to qualify for this important judicial position, different election models, and the length of judicial mandates. After providing an overview of the comparative law solutions on this matter, the author focuses on the rules provided in the Constitution of the Republic of Serbia (2006). The aim of the research is to analyze the existing constitutional and legal provisions of other countries and compare them with the provisions in Serbia in order to address the following question: what is the key to the survival of this institution as an independent, impartial, politically neutral and professional authority.
Keywords: constitutional judiciary; election; independence; Constitutional Court of the Republic of Serbia